Pengembangan Aplikasi Peta Interaktif Tiga Dimensi Studi Kasus Fakultas Ilmu Komputer Universitas Brawijaya - Raesulli Kautsar Riando; Buce Trias Hanggara; Agi Putra Kharisma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
The increased usage of virtual applications as a replacement for many real world activities has risen significantly with the advance of technology. Due to the many benefits of virtual alternatives of real world activities, therefore rises the need of the development of a virtual representation of the FILKOM UB campus area. The visual representation of the FILKOM UB campus area takes shape in a 3D virtual map. The map has plenty of objects that enhances the realism of the virtual area, the objects also adds additional information to the map. The virtual map application contains two modes, an exploration mode and a 3D map mode. With the two modes, the user is able to more freely explore the virtual FILKOM UB campus area. The development of the virtual map application is split into stages such as data collection, analysis, design, and implementation. The virtual map application is made using the Unity3D game engine, the decision to choose this game engine is based on the relative simplicity of the application and the ability of the game engine to display realistic graphics. The objects used on the virtual map were made in blender3D. The application runs on desktop and laptop computers, this decision was chosen because of the limitation of mobile devices hampering the functionality of the application. Testing results shows the application was able to complete all the functional requirements with great results.